Assessing the Effectiveness of Immunoelectric Method in Detecting Mycobacterium avium Subspecies paratuberculosis in Cow Faeces With Paratuberculosis - Mohammad Khosravi; MohammadRahim Haji Hajikolaei; Mohammad Nouri; Shayan Kalanter (Veterinary Medicine and Science)
ABSTRACT Mycobacterium avium subspecies paratuberculosis (MAP), the causative agent of Johne's disease in ruminants, is typically transmitted through the faecal–oral route. This study aimed to optimize and evaluate an immunoelectric (IE) method for detecting MAP in faecal samples from infected cows. The necessary polyclonal antibodies were extracted from hyperimmune donkeys and rabbits using affinity chromatography. Furthermore, cross‐reactive antibodies were eliminated through absorption with Mycobacterium phlei. The binding of donkey antibodies to a polystyrene filter and rabbit antibodies to Fe nanoparticles was facilitated by a diethylenetriaminepentaacetic acid (DTPA) linker. The trapping of bacteria on the filter and the fixation of Fe nanoparticles attached to specific antibodies led to a modification in the electrical resistance of the filter. This alteration in electrical resistance can be quantified using a high‐precision electrical meter. In this research, MAP was identified through both polymerase chain reaction (PCR) and the IE methods in faecal samples from dairy cows, producing varied outcomes in the enzyme‐linked immunosorbent assay (ELISA) test. The sensitivity and specificity of the ELISA approach for detection of the serum antibodies in comparison to the PCR technique were determined to be 75% and 72%, respectively. In contrast, the sensitivity and specificity of the IE method relative to the PCR approach were found to be 96% and 95%, respectively. With a detection time of less than 60 min, cost‐effectiveness per sample, user‐friendly operation utilizing an IE device, no requirement for specialized machinery and applicability in farm or dairy settings, this technique emerges as a promising alternative to traditional bacterial detection methods.